9 - The State of the Process of Decentralisation in Cameroon - Cheka, Cosmas (Africa Development, 2007)
The pace of the process of decentralisation in a given context unavoidably depends on the degree of favourableness of the legal environment and the dynamism of stakeholders (especially of local authorities, the state, develop- ment cooperation partners and civil society). This paper seeks to inform on the state of the process in Cameroon by exposing its current legal environment, its constraints and the level of organisation of its key actors in relation to the legal environment. Drawing from this assessment, the paper assesses the shortcom- ings of the decentralisation process in Cameroon while arguing that the objec- tive for embarking on decentralisation in each context varies with its promoter. In the case of Cameroon, decentralisation constitutes the legal, institutional and financial means through which regional and local authorities operate to foster local development with the active involvement of the population. Through the devolution of powers to local entities, local development could be enhanced and a contribution made to the fight against poverty. The assessment of the legal framework and of its stakeholders shows that the decentralisation laws passed in 2004 in Cameroon have local development and governance as their main thrust. The new laws certainly create an environment that represents an irreversible step forward for the process of decentralisation but are in need of completion by the passing of legal instruments of application for them to effec- tively accelerate the pace of the decentralisation process and good governance. There is also need for better organisation and coordination of interventions of the stakeholders. The process is currently hampered by especially financial constraints on local authorities and limited capacities of the actors and benefici- aries of devolved powers. The paper concludes with a plea in favour of inter alia the strengthening of the capacities of all stakeholders through an approach that is sustainable if the objective of decentralisation is to be met.